THE ROLE OF COMMUNITY FIGURES IN THE FORMATION OF ADOLESCENT PERSONALITY OF TANJUNG VILLAGE, BATHIN VIII DISTRICT, SAROLANGUN DISTRICT - Zuli Azwen; Elvina Safitri (Dinasti Publisher, 2019)
This study aims to determine the role of community leaders in shaping the personality of adolescents, the efforts made by community leaders, as well as the obstacles faced in the formation of the personality of teenagers in Tanjung Village. The method used in this research is qualitative method. The research background is located in Tanjung Village, District Bathin VIII, Sarolangun District. Data collection techniques used are observation, interviewand documentation. The results of this study indicate that: The role of community leaders in the formation of adolescent personality is good, by olding programs specifically designed for adolescents so that teenagers can follow and can avoid the form of juvenile delinquency, as well as cooperating with parents as people in the first example by his child. Data collection techniques are through informants. The stages in analyzing the data are: reduction, data presentation and conclusion making. Based on the results of this study indicate the state of personality of adolescents is not good, the efforts made by community leaders in shaping the personality of adolescents in entrepreneurship is good, the obstacles faced come from adolescents, teenage parents, youth education, and communication and information technology that makes adolescents difficult to entrepreneurship. In conclusion, community leaders can shape the personality of adolescents in entrepreneurship, but it must be supported by teenagers and teenage parents themselves. His advice to community leaders must never stop making activities that can make teenagers' personality in entrepreneurship better.